Morphometric Study of Suprascapular Notch in Indian Dry - Venkateswara Rao, Madala; Hema, Lattupalli (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The suprascapular notch is a semicircular notch at the superior border of scapula, just medial to the base of the Coracoid process, is bridged by the superior transverse scapular ligament, which is sometimes ossified and the foramen which is thus completed, transmits the suprascapular nerve to the supraspinatus fossa. Variations in the morphology of suprascapular notch have been identified as one of the causes of suprascapular nerve entrapment.